Construction of Free Hardware Device for Interaction in 3D Environments - Rodríguez Jiménez, Jorge Enrique (2021)
This article presents two models of design and construction of a device for the simulation of the movements and interaction of the upper and lower limbs in three-dimensional environments (Virtual Reality device), through the use of free technologies. The Arduino hardware platform is used as the physical data acquisition center. The selection of sensors and actuators is carried out, as well as an analysis of their feasibility and functionality.